Systems Analysis of the Liver Transcriptome in Adult Male Zebrafish Exposed to the Plasticizer (2-Ethylhexyl) Phthalate (DEHP) - Huff, Matthew (Sci Rep, 2018)
The organic compound diethylhexyl phthalate (DEHP) represents a high production volume chemical found in cosmetics, personal care products, laundry detergents, and household items. DEHP, along with other phthalates causes endocrine disruption in males. Exposure to endocrine disrupting chemicals has been linked to the development of several adverse health outcomes with apical end points including Non-Alcoholic Fatty Liver Disease (NAFLD). This study examined the adult male zebrafish (Danio rerio) transcriptome after exposure to environmental levels of DEHP and 17α-ethinylestradiol (EE2) using both DNA microarray and RNA-sequencing technologies. Our results show that exposure to DEHP is associated with differentially expressed (DE) transcripts associated with the disruption of metabolic processes in the liver, including perturbation of five biological pathways: ‘FOXA2 and FOXA3 transcription factor networks’, ‘Metabolic pathways’, ‘metabolism of amino acids and derivatives’, ‘metabolism of lipids and lipoproteins’, and ‘fatty acid, triacylglycerol, and ketone body metabolism’. DE transcripts unique to DEHP exposure, not observed with EE2 (i.e. non-estrogenic effects) exhibited a signature related to the regulation of transcription and translation, and ruffle assembly and organization. Collectively our results indicate that exposure to low DEHP levels modulates the expression of liver genes related to fatty acid metabolism and the development of NAFLD.